Analysis of production schedules and sequencing through simulations in Preactor as Express 2016® software to reduce delivery delays in a metallurgical company - Saldanha, Marcos Felipe Bonifácio; de Paula, Gabriel Carrara Theodoro Garcia; Lopes, Paulo Henrique Silva (Brazilian Journal of Production Engineering, 2021)
Considering that companies live in a more aggressive and dynamic competitive scenario; production management becomes increasingly necessary. Therefore, the programming and sequencing of production appear as differentials with respect to factors of extreme importance in a production line. In this context, the focus of this work was to use the software Preactor AS Express 2016® to simulate the current sequencing method of the company and, also, other methods offered by the software, in order to find the one that was more agile and efficient. The methodology used was the case study focusing on a specific customer of the company, which represents 74,02% of the annual turnover. The data was obtained through the collection and documentary analysis of the data of the production orders of this client in the months of September and December 2019, these being the biggest participation of the client in the year. The data were imported into the software and different alternatives were analyzed, after these analyzes it was possible to identify that the sequencing alternative used by the company was feasible in months whose production times were higher, the proposed method was efficient even in more emerging months. Finally, it was concluded that the sequencing method used by the company is not the most appropriate, given that emerging months are more common throughout the year, so it is recommended for the company to use the Backwards by order of delivery method.